A diagnostic marker for childhood apraxia of speech: the coefficient of variation ratio. - Shriberg LD; Green JR; Campbell TF; McSweeny JL; Scheer AR (Clinical Linguistics & Phonetics, 2003)
Terms such as isochrony, syllable segregation, scanning speech and staccato-like rhythmic quality have been used to characterize the temporal regularity that may be a core feature of apraxia of speech. The present report describes a procedure to quantify temporal regularity in children with suspected apraxia of speech (sAOS). Conversational speech samples from 15 such children, together with samples from 30 3-6-year-old children with normal speech acquisition and 30 3-6-year-old children with moderate to severe speech delay of unknown origin, were selected from an audio archive. Signal processing routines were developed to identify and measure the duration of speech and pause events in 24 utterances from the speech samples of each of the 75 speakers. A value termed the coefficient of variation expressed the normalized variability in the durations of each participant's speech events and pause events within each utterance. A metric termed the coefficient of variation ratio, derived by dividing the coefficient of variation for pause events by the coefficient of variation for speech events, expressed a speaker's relative temporal variation in the two domains. The 15 children with sAOS had higher coefficient of variation ratios than the 30 children in each of the two comparison groups, indicating that the children with sAOS had proportionally more variation in the duration of pause events and/or less variation in the duration of speech events. Findings are interpreted as supporting the view that a constraint in speech timing is a core feature of the praxis disorder that defines a developmental form of apraxia of speech.